2013
DOI: 10.1515/znc-2013-7-805
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents and Biological Activities of Galinsoga parvifl ora Cav. (Asteraceae) from Egypt

Abstract: The phytochemical investigation of an aqueous ethanolic extract of Galinsoga parviflora Cav. (Asteraceae) resulted in the isolation and identification of eleven compounds namely: triacontanol, phytol, β-sitosterol, stigmasterol, 7-hydroxy-β-sitosterol, 7-hydroxystigmasterol, β-sitosterol-3-O-β-D-glucoside, 3,4-dimethoxycinnamic acid, protocatechuic acid, fumaric acid, and uracil. Furthermore, 48 volatile constituents were identified in the hydrodistilled oil of the aerial parts. The ethanolic extract at a cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Most of the identified bioactive compounds possess remarkable medicinal qualities for the management of medical conditions such as malaria, flu, cold, colorectal cancer, liver ailments and skin diseases. The investigation of plant extracts revealed the presence eleven bioactive compounds including compounds 7, 9,12, 13, 14, 15, and 22 [ 14 ]. Similar study identified 48 bioactive compounds from hydrodistilled oil of the aerial parts of G. parviflora , where compound 29 being the most abundant component (45.66%), followed by compounds 27 (4.99%), 30 (4.95%), and 22 (4.39%) [ 14 ].…”
Section: Phytochemistry Of G Parvifloramentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the identified bioactive compounds possess remarkable medicinal qualities for the management of medical conditions such as malaria, flu, cold, colorectal cancer, liver ailments and skin diseases. The investigation of plant extracts revealed the presence eleven bioactive compounds including compounds 7, 9,12, 13, 14, 15, and 22 [ 14 ]. Similar study identified 48 bioactive compounds from hydrodistilled oil of the aerial parts of G. parviflora , where compound 29 being the most abundant component (45.66%), followed by compounds 27 (4.99%), 30 (4.95%), and 22 (4.39%) [ 14 ].…”
Section: Phytochemistry Of G Parvifloramentioning
confidence: 99%
“…It is commonly employed for the management of both infectious and non-infectious diseases. Phytochemicals such as quercetin, beta sitosterol, gallic acid, kaempferol and hydrobenzoic acid have been identified from G. parviflora [ 14 ]. It has potential pharmacological properties including antibacterial [ 15 ], antimalarial [ 16 ], anti-oxidant [ 17 ], antidiabetic [ 14 ] and anti-inflammatory [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies indicate that G. parviflora exhibits a diversity of flavonoids derived from caffeic acid, steroids, among others [8], [55], [56] which is in accordance to the study of Bazylko et al [57], with ethanolic extract, that identified phenolic acids, such as caffeic, caffeoylquinic and dicafeoylquinic acid, using HPTLC; and also in accordance to the results of Dudek et al [55], with hydrophilic extract of aerial parts, that identified substances derived from caffeic acid, such as 5-O-caffeoylquinic acid (chlorogenic acid), 1, 3-O-dicaffeoylquinic acid, 3, 5-Odicafeoilquin, using spectrometric techniques. Meanwhile, the findings presented in our study (Table 5) corroborate those reported by Mostafa et al [56] and Anwar et al [58] that indicate the presence of stigmasterol, β-sitosterol and β-sitosterol in G. parviflora extracts. In addition, caffeic acid derivatives found in G. parviflora has been identified as an important protective factor for dermal fibroblasts against oxidative stress induced by ultraviolet radiation (UVA), by activating the cellular antioxidant system in a study by Parzonko and Kiss [59].…”
Section: Chemical Analysis Of V Polyanthes and G Parviflora Extractsmentioning
confidence: 99%
“…Moreover, the oral consumption of this extract treat symptoms of common cold, flu, and cold sores. 16,17 It also exhibits significant antibacterial, 18 antifungal, 19 and antiviral 20 properties. On the other hand, CQ belongs to Vitaceae and is spread throughout India.…”
Section: Introductionmentioning
confidence: 99%